Defining the Carceral Characteristics of the ‘Dickensian prison’: A Corpus Stylistics Analysis of Dickens’s Novels - March, Eleanor; Moran, Dominique; Houlbrook, Matt; Jewkes, Yvonne; Mahlberg, Michaela (Victoriographies, 2023)
Charles Dickens is often evoked to make connections to Victorian times – and to highlight the need for change in today’s society. The situation of prisons is a prime example, where references to the ‘Dickensian prison’ figure in contemporary discourse to draw critical attention to the state of prisons and to call for reform. But it would be too simple to assume that today’s references to the Dickensian prison relate directly to the way Dickens narrates the prison. Therefore, this paper presents a detailed digital humanities textual study of prisons in Dickens’s novels to shed light on the vocabulary that the author uses to talk about this institution. The prisons in Dickens’s novels tend to be historic and outdated prisons, rather than the new Victorian-built model prisons. Using the CLiC (Corpus Linguistics in Context) web app, which combines a set of corpora with tools to access and search sets of texts, we set out to accumulate a substantial amount of textual evidence for a description of the carceral characteristics of Dickens’s prisons. These characteristics describe features of the prison building, prison TimeSpace, prison life, and effects of the prison. Our findings present a valuable platform from which to consider the enduring popularity of the Dickensian prison in contemporary penal discourse.
CRIS-Team Scopus Importer:2024-03-27
Keywords: carceral; confinement; corpus stylistics; Dickens; imprisonment; prison